2017
DOI: 10.1111/epi.13845
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of active uPA and KLK8 assessed by [111In]MICA‐401 binding correlate with the seizure burden in an animal model of temporal lobe epilepsy

Abstract: Strong association of reduced [ In]MICA-401 binding with seizure burden in the KASE model suggests that analysis of reduced levels of active uPA/KLK8 represents a novel biomarker candidate to be explored as a biomarker for epilepsy severity. However, limited BBB permeability of [ In]MICA-401 currently limits its application in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Complete deficiency of Neuropsin has been shown to shift the E-I balance in vivo towards excitation, in the hippocampus of mice treated with kainic acid, thus leading to a more severe progression of the status epilepticus than in control [13]. Similarly, in an animal model of epilepsy, a pathological condition associated with strong recurrent excitation, we have recently found that the frequency of seizures is higher in epileptic rats that show a more pronounced decrease in active uPA and Neuropsin [40]. While our results do not unanimously point to a shift of the E-I balance in either direction, the inhibition of uPA and Neuropsin certainly had a profound effect on the dynamics of the network.…”
Section: Discussionmentioning
confidence: 76%
“…Complete deficiency of Neuropsin has been shown to shift the E-I balance in vivo towards excitation, in the hippocampus of mice treated with kainic acid, thus leading to a more severe progression of the status epilepticus than in control [13]. Similarly, in an animal model of epilepsy, a pathological condition associated with strong recurrent excitation, we have recently found that the frequency of seizures is higher in epileptic rats that show a more pronounced decrease in active uPA and Neuropsin [40]. While our results do not unanimously point to a shift of the E-I balance in either direction, the inhibition of uPA and Neuropsin certainly had a profound effect on the dynamics of the network.…”
Section: Discussionmentioning
confidence: 76%
“…Neuropsin deficiency impairs the activation of ErbB4 positive GABAergic interneurons (Figure 5), resulting in hyper-activity of pyramidal neurons in the stimulated state and breakdown of the neuronal excitation-inhibition balance in hippocampal networks [20]. Supporting this theory, a recent study shows that reduced levels of active neuropsin are observed in CA1-CA3 subfields of the hippocampus, dentate gyrus, extrahippocampal temporal lobe and parietal cortex during spontaneous seizures in kainic acidinduced status epilepticus rats [37].…”
Section: The Neurobiology Of Neuropsinmentioning
confidence: 84%
“…Neural extracellular matrix functions have been linked with epilepsy . The expression of urokinase‐type plasminogen activator and kallikrein‐related peptidase 8, proteins involved in remodeling of the matrix proteins, is reduced in a rodent model of temporal lobe epilepsy, and this reduced expression is related inversely with seizure burden in epileptic animals …”
Section: Possible Epileptogenic Mechanisms Influenced By Microglial Pmentioning
confidence: 99%